Governance Risk Compliance Integration in Analyzing Determinants of Audit Report Lag - Novia Wijaya; Anastasia Angelica Halim (Universitas Pendidikan Ganesha, 2025)
Despite rapid technological disruption and strict regulatory deadlines, there remains limited empirical understanding—particularly in the Indonesian context—of how governance, risk, and compliance (GRC) mechanisms, internal audit leadership characteristics, and firm risk factors jointly influence audit report lag and the timeliness of audited financial reporting. This research aims to acquire empirical evidence on the relationship between audit report lag and various determinants, including earnings volatility, financial distress, internal audit attributes, company size, income sign, and income smoothing, while integrating the governance–risk–compliance (GRC) framework with traditional audit risk factors. Using 440 observations from 110 non-financial firms listed on the Indonesia Stock Exchange (2019–2022) and multiple regression analysis through IBM SPSS Statistics 25, results reveal that financial distress, key audit matters (KAM) disclosure, company size, and income sign significantly affect audit report lag. Financially stable and large companies experience faster audit processes, while loss-making clients are subject to more scrutiny. KAM disclosure fosters auditor accountability, promoting timely, high-quality audits. These findings emphasize the novelty of combining GRC perspectives with established determinants, offering a more holistic approach for reducing audit delays, enhancing transparency, and strengthening investor trust.